Alexander Mavroyeni Bey: From the 19th century reform era to the young Turk revolution through the life and ideology of a neophanariot Ottoman Bureaucrat - Andrianopoulou, Konstantina. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2004., 2004)
The 19th century and the beginning of the 20th had been of pivotal importance for the Ottoman Empire. The reforms and the social- political alterations the country underwent changed drastically the scenery. Among the different points of view that one can adopt in order to approach and examine what was going on in the Ottoman Empire during this period, the issue of the non Muslim Ottoman communities presents peculiarities and particularities that could help us understand both how the Ottoman State responded to the problem its multiethnic character posed in a era of national building, how these communities reacted to the solutions adopted and in what ways these changes affected them .The present work tries to unfold aspects of this problematique through the example of a Greek Orthodox Ottoman bureaucrat of Istanbul: Alexander Mavroyeni Bey. Through his personal writings -an example of his intimate thoughts and notes, which constitutes a special kind of primary source- and his discourses in the Ottoman Senate -an example of his official writings-, all of which are written during the first two decades of the 20th century, we will try to shed some light in the changes both the Millet-i Rum and the Ottoman Empire were undergoing. During our analysis, we will deal with Mavroyeni Bey's case as a particular representative of a specific power group-class and tradition inside the Greek Orthodox millet and the Ottoman state -that of the Neophanariots-, and we will try to understand his position in relation to the Ottoman power center, to the head of his respective community, as well as to the Greek state, that from the late 19th century was enhanging its role on the Greek Ortrhodox population of the Empire. We will also try to examine his ideological orientations concerning the past and the future of both the Ottoman state and the Greek Orthodox millet, as well as his ideological response to the changes in the aftermath of the Young Turk revolution.
Keywords: Greeks -- Turkey -- Political activity.; Turkey -- Politics and government.; Turkey -- Officials and employees.